2013
DOI: 10.1039/c3cp52823e
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of TiO+ with water: infrared photodissociation spectroscopy and density functional calculations

Abstract: We investigated the interaction of TiO(+) with water by conducting infrared photodissociation spectroscopy and density functional theory calculations on TiO(H2O)Ar(+) and TiO(H2O)5-7(+) clusters. The studies show that TiO(H2O)Ar(+) has two isomers, Ti(OH)2Ar(+) and (H2O)-TiOAr(+), coexisting in our experiments. The structure of TiO(H2O)5(+) is characterized by attaching four water molecules to a Ti(OH)2(+) core with their O atoms interacting with the Ti atom directly. With the increasing number of water molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Infrared photodissociation spectroscopy and density functional theory (DFT) calculations of the interaction of TiO + with water, demonstrate that a Ti(OH) 2 + type product is dominant for this process. 42 The structure of neutral (TiO 2 ) n (n = 2-13) clusters 43 and reliable values for the heats of formation of small (TiO 2 ) n (n = 1-3) clusters 44 have been reported. These structures and energies can be useful for understanding the general chemistry of (TiO 2 ) n species.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Infrared photodissociation spectroscopy and density functional theory (DFT) calculations of the interaction of TiO + with water, demonstrate that a Ti(OH) 2 + type product is dominant for this process. 42 The structure of neutral (TiO 2 ) n (n = 2-13) clusters 43 and reliable values for the heats of formation of small (TiO 2 ) n (n = 1-3) clusters 44 have been reported. These structures and energies can be useful for understanding the general chemistry of (TiO 2 ) n species.…”
Section: Introductionmentioning
confidence: 93%
“…Numerous experimental [25][26][27][28][29][30][31][32] and theoretical [33][34][35][36][37][38][39][40][41][42] studies have been reported for isolated, neutral and charged titanium oxide clusters with the intent of correlating their structures and properties with those of the bulk. For example, Zhai et al 25 have studied the electronic structure and band gap evolution of (TiO 2 ) n À (n = 1-10) clusters, employing photoelectron spectroscopy, to gain mechanistic understanding of TiO 2 surface defects and photo-catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51][52][53] There has been substantial progress made in understanding the structure and reactivity of small metal oxide clusters, [54][55][56][57][58][59] including several studies on the interaction between titanium dioxide clusters and water molecules. [60][61][62][63] Of particular relevance is the work of Zheng and co-workers, who performed anion photoelectron spectroscopy (PES) on the anionic (TiO 2 )(H 2 O) 0-7 clusters and inferred that dissociative adsorption of water occurs to form a hydroxide species. 61 We recently reinvestigated the (TiO -2 )(H 2 O) system using slow electron velocity-map imaging of cryogenically cooled anions (cryo-SEVI), a high-resolution form of anion PES, coupled with detailed computational simulations.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Since atomic and molecular clusters can be regarded as models for understanding the fundamental mechanisms in condensed phases and on complex surfaces, numerous studies have been carried out to investigate the hydrated metal-oxide clusters and their corresponding isomers. [35][36][37][38][39] These studies suggested that metal oxides interacting with water can form hydrated metal-oxides or under water dissociation to produce the corresponding hydroxyl species. Recently, we have investigated the interaction of Co n O − with water and found that they prefer to exist in the form of Co n (OH) 2 (H 2 O) n − .…”
Section: Introductionmentioning
confidence: 99%